Malaysia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper undertakes a brief examination of poverty trends in Malaysia since the early 1970s and the policies that may have contributed to its reduction. The paper presents trends in poverty, and describes some of the policies that may have generated the poverty outcome. It analyzes the legal framework for bankruptcy and insolvency, highlighting that the legal framework in Malaysia appears to be generally comprehensive, especially by regional standards, and has been largely modeled on the United Kingdom system.